2016
DOI: 10.3390/su8070689
|View full text |Cite
|
Sign up to set email alerts
|

Regional Port Productivity in APEC

Abstract: Abstract:The regional growth of the goods and services trade has placed greater pressure on the ports of the Asia-Pacific Economic Cooperation (APEC) members, especially in the developing countries. The purpose of this study is to apply the generalized metafrontier Malmquist productivity index (gMMPI) to compare the port productivity of developed countries (DCs) and developing countries (LDCs) in APEC. The results indicate that, first, the average rate of utilized capacity among the ports of APEC members was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
3
0
4
Order By: Relevance
“…This is consistent with the findings of Gao, Xu, Ruan and Lu [9], who found that selection of the study site depends largely on the size of gross domestic product (GDP). GDP grows faster in India, China, South Korea, and Taiwan than in Western countries [8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is consistent with the findings of Gao, Xu, Ruan and Lu [9], who found that selection of the study site depends largely on the size of gross domestic product (GDP). GDP grows faster in India, China, South Korea, and Taiwan than in Western countries [8].…”
Section: Discussionmentioning
confidence: 98%
“…Among the activities in various sections of a supply chain, such as purchasing, material management, production, distribution, and marketing, one of the biggest challenges is meeting customer requirements while managing costs. Depending on the economy's level of development, the total supply chain cost accounts for, on average, approximately 5% to 10% of a company's annual income [6][7][8]. According to the GMA 2010 Logistics Benchmark Report, effectively reducing logistics costs has become a major goal for supply chains of US companies in 2008 and 2010 [7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to efficiency, port/terminal productivity is a measure primarily observed with an emphasis on changes over time (for instance, how fast cargo is handled), expressed by the amount of output obtained for input used [24]. Productivity levels differ for each port due to their infrastructure, service quality and the ability to attract demand [25]. Consequently, efficiency indicates the need for technical improvement, while productivity refers to increasing efficiency in the industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Así también Wu et al (2016) analizan la productividad de los puertos de las economías del apec. Para ello emplean la metodología del índice de productividad de Malmquist (1953) de metafrontera generalizada, para comparar la productividad portuaria de países desarrollados y países en desarrollo en el apec.…”
Section: Estado Del Objeto De Estudiounclassified
“…En particular, por su importancia la región del apec ha sido objeto de diversos estudios relacionados con la eficiencia y productividad. En los últimos 15 años se pueden encontrar algunos relacionados con la productividad y el crecimiento económico (Wu, 2004); con ahorro energético y su eficiencia (Jin-Li & Chih-Hung, 2007); con la eficiencia del transporte (apec Secretariat, 2008); con el sector agropecuario (Ayvar et al, 2018;Yu et al, 2011); con las telecomunicaciones (Chun-Hsiung & Chun-Yu, 2012); con los puertos y las aduanas (Delfin & Navarro, 2017;Infante & Gutiérrez, 2013;Wu et al, 2016;Zamora, 2017), o incluso con el medio ambiente (Wang et al, 2016).…”
Section: Introductionunclassified